Comparison of selected human reliability assessment methods on the example of a collective water supply system operator - Żywiec, Jakub; Tchórzewska-Cieślak, Barbara (Instal, 2023)
Specialist literature indicates a large share of the human factor among the causes of failures of technical systems at the level of 70 to 90%, depending on the analyzed sector. For collective water supply systems (CWSS) it is estimated that human activity is the cause of 75% of failures. In the 1960s, the idea of operator reliability research as one of the most important elements of a biotechnical system was born. Over the years, over 50 different methods of assessing operator reliability (HRA – Human Reliability Assessment) have been developed, which differ in their properties and applicability for selected systems. During this period, HRA methods developed towards a better fit to the real working conditions of the operator. The differences between the individual methods allowed them to be divided into three generations. The first generation methods (1970 – 1990) focus on determining the probability of operator error. The second generation of methods (1990 – 2005) takes into account the impact of contextual factors describing the situation and human cognitive functions on the level of operator reliability. The third generation of methods (2005–present) focuses on the use of simulation methods to assess operator reliability. The paper presents selected methods for assessing operator reliability. Each of them comes from a different generation, to present the most important differences between them. The selected HRA methods were compared in terms of the method of determining the probability of operator error, the impact of factors describing the context, the impact of expert judgment and their use in various fields. An assessment of thereliability of the CWSS operator for the filter backwashing process was carried out using selected methods, and then the obtained results were compared with each other.